Some aspects of biology of Oreochromis niloticus L. (Perciformes: Cichlidae) recently introduced in Lake Toho (Benin, West Africa). - AHOUANSOU, MONTCHO SIMON; LALEYE, PHILIPPE A. (My University, 2008)
In 1995, Oreochromis niloticus was accidentally introduced in Lake Toho by means of fish farming developed around this lake. The present study was carried out to provide information on the growth, condition factor and reproduction of this species in the new environment. The length-weight relationship was W = 0,0156TL3.067 (r² = 0.98) for male and female. The slope b of this relationship, was not different from 3 (t = 1.73, p = 0.225). This indicates that the growth of this species is isometric. The condition factor of the species from 0.82 to 2.02 (average: 1.49 ± 0.34) depends on the sex. There was no significant difference between rainy and dry seasons related to the condition factor. The spawning occurred throughout the year but was intensive from June to November. The sex ratio is 1.3:1 in favour of males. The size at first sexual maturity was estimated to be 9.1 cm for females and 12.9 cm for males. The absolute fecundity varied from 246 to 2453 oocytes per fish. These results confirm a successful establishment of O. niloticus in Lake Toho.
Keywords: Oreochromis niloticus; condition factor; reproduction; Lake Toho; Benin.